2021
DOI: 10.1016/j.biochi.2021.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics prediction of emerging notable spike protein mutations in SARS-CoV-2 implies a need for updated vaccines

Abstract: The spike protein of SARS-CoV-2 plays a crucial role in binding with the human cell surface, which causes its pathogenicity. This study aimed to predict molecular dynamics change of emerging variants in the spike protein. In this study, several structural biology tools, such as SuperPose, were utilized to study spike protein structures' thermodynamics, superimposition, and the spike protein disulphide bonds. This questions the current vaccines efficacies that were based on the Nextstrain clade 19A that first d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…[13] A possible reformulation of the vaccines adjusted to currently circulating lineages of SARS-CoV-2 is being investigated. [14] , [15] , [16] The deployment of vaccines clearly remains the best public health measure to control the spread of SARS-CoV-2 and the severe health effects of COVID-19. [17] , [18] …”
Section: Introductionmentioning
confidence: 99%
“…[13] A possible reformulation of the vaccines adjusted to currently circulating lineages of SARS-CoV-2 is being investigated. [14] , [15] , [16] The deployment of vaccines clearly remains the best public health measure to control the spread of SARS-CoV-2 and the severe health effects of COVID-19. [17] , [18] …”
Section: Introductionmentioning
confidence: 99%
“…Although of significant value, even the currently available vaccines are not without occasional serious side effects [26][27][28]. Moreover, the efficacy of the vaccines has decreased as the virus has mutated [29,30]. Already, there are several variants that have been identified and there will likely be others that may further reduce the effectiveness of the vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…The T478K was reported as a mutation in the functional Receptor Binding Domain (RBD) associated with the infectivity and pathogenicity of any variants, where is it found ( Jhun et al, 2021c ). The biological meaning of this is that the previously reported mutation D614G was the reason for giving the spike protein a tendency to increase transmissibility and alter BNT162b2 vaccine-elicited neutralization when compared with the wild type spike protein without D614G ( Al-Zyoud and Haddad, 2021a ; Plante et al, 2021 ; Isabel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 77%
“…No available data about G446 and T547K however, it was reported that G496S and Q493R, and Q498R have formed new salt bridges with residue D38 of the Angiotensin Converting Enzyme (ACE2) ( Mannar et al, 2022 ). It is worth mentioning here that the Omicron mutation E484A has increased the spike protein flexibility in a higher value of ΔΔS ENCoM value, giving 0.762 kcal.mol −1 .K −1 when compared with E484Q with a value of ΔΔS ENCoM value giving 0.389 kcal.mol −1 .K −1 and E484K with a value of ΔΔS ENCoM value giving 0.490 kcal.mol −1 .K −1 ( Al-Zyoud and Haddad, 2021a ), the mutation in amino acid 484 was previously reported as a mutation confer antibody resistance ( Liu et al, 2021a ). Specifically, it was reported that the mutation Q493R has conferred a simultaneous resistance to the treatment by the monoclonal antibodies, namely Bamlanivimab and Etesivimab ( Focosi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 93%